Assessing The Contribution Of Tourism To Economic Growth In Nepal - Ojha, Krishna Prasad; Kandel, Madan; Shah, Kapil (Journal of Islamic Economics Perspectives, 2024)
This study examines the impact of tourism on Nepal’s economic growth using time-series data from 2001 to 2024. Employing linear and multiple regression analyses, results show a significant upward trend in tourist arrivals, increasing by approximately 1,493 visitors annually, and a corresponding rise in tourism’s contribution to GDP by 0.0184 percentage points per year. A strong positive correlation (r = 0.87) between tourist arrivals and GDP contribution underscores tourism’s key role in economic development. Despite a sharp decline in tourism during 2020 due to the COVID-19 pandemic, structural break analysis indicates a resilient recovery in subsequent years. Stationarity tests show that important variables were not stable, so we adjusted the data to make it suitable for accurate time-series modeling. Findings highlight the sustained and growing economic importance of tourism in Nepal and suggest avenues for future research incorporating advanced modeling techniques.